Target costing implementation decision and organizational capabilities from the perspectives of the balanced scorecard model: a study on Malaysian automotive industry / Hussein Hussein Hamood Sharaf Addin - Sharaf Addin, Hussein Hussein Hamood (2015)
Target Costing (TC) is not only seen to be related to product cost reduction. Instead, it includes product quality, functionality and lead time which, to a similar extent, should be seriously considered. Organizational Capabilities (OCs), as a contextual variable, could affect organizational functions when particularly supported by Balanced Scorecard (BSC) perspectives model in relation to TC objectives. The main objective of this study is to assess TC implementation decision and OCs from the perspectives of the BSC model. Four specific research questions are recaptured in this study, which are in tandem with four specific research objectives formulated to support the main objective of the study. The first three specific objectives focus respectively on the business environment influencing TC-related changes, the practical level of TC implementation stages from the perspective of "financial" and "non-financial" OCs measures, and the applicability level of integrating TC indicators within the BSC model. The fourth specific objective examines the effect of OCs on TC implementation decision as well as the extended effect of TC implementation decision on ultimate organizational performance, From the 515 questionnaires distributed, a total of 201 questionnaires were collected and finally, a total of 176 questionnaires were used. The findings showed: First, significant changes were made during the past five years in TC-related aspects including price structure, cost structure, and product structure. Second, the findings showed excellent ability towards TC implementation stages, except for some capabilities that required TC follow-up activities in achieving cost reduction objectives, especially for Car makers as well as when employing the Confrontation strategy. Third, the findings showed an acceptable ability towards integrating TC indicators within the BSC's perspectives associated with higher ability of Parts and Components makers as well as when employing the Confrontation strategy. Finally, through specific hypotheses testing, the findings showed a positive and significant effect of OCs on TC implementation decision which is significantly non-invariant across the two types of industries and significantly moderated by Non-Confrontation strategies (Cost Leadership and Differentiation). Further, a significant and positive extended effect was found for TC implementation decision on ultimate organizational performance. The findings overall conclude that the company strategy and industry type are main determinants for TC involvement. The main contributions of the study include: applying BSC's perspectives to measure OCs (literature), using company strategy as a moderating variable, using industry type as a control variable, Rasch Model analysis in the pilot study as well as in the main study using its outputs as implications for SEM analysis (methodology), and providing further understanding on integrating TC and BSC as well as developing a conceptual framework for the integration of TC and OCs from BSC generation model based on the findings' (knowledge/findings).